Homens à deriva: a representação da masculinidade em dois romances de Daniel Galera - Xavier, Luiz Gustavo Osório (2020)
The main objective of this work is to analyze the construction, representation and (re)affirmation of traditional models of masculinity in two novels by Daniel Galera, adopting a perspective linked to social sciences and gender studies, using the works of Butler (2017), Connell and Messerschmidt (2013), Grossi (2004), Lehnen (2013), Louro (2000, 2013), Machado (2001), Oliveira (2004), Schøllhammer (2009), among others, as a theoretical framework. In general, the work of Daniel Galera presents characters without direction in the contemporary world and in conflict with their identities. The two novels chosen for analysis, The shape of bones (2006) and Blood-drenched beard (2012), allow an in-depth study on the construction, representation and (re)affirmation of traditional models of masculinity, because in both narratives the main characters manifest conflicts with their identities that are marked by gender issues. In both novels, the protagonists perform roles that are more aligned with masculine patterns that does not suit their subjectivities. In the case of the former, the pattern is highly influenced by media productions and subjects external to the protagonist's family nucleus; in the case of the second, the protagonist is influenced by members of his family, especially his grandfather. With the analysis of the novels, it was observed the literary representation of the constitution of the masculinity of the central characters, of how it is traversed by intersectional variables, and how it is carried out through different performances that, in turn, are traversed by the fantasies of the characters. In addition, it was observed how the narrative strategies used in the two novels contribute to the presentation of the protagonists' performance. In The shape of bones (2006), the performance of the central character is due to a lack of contact with his own interiority and his desire for adequacy and social recognition, which leads him to represent, during his youth, the role of “Horse Hands”, and, during adulthood, the roles of plastic surgeon, husband and father. This evidence, therefore, the intersection of the generational variable with masculinity, since the masculine ideals that are adopted by the protagonist are different throughout his life. In Blood-drenched beard, the plot is associated with a family nucleus, and the father's announced suicide is what motivates the central character to investigate his grandfather's death. In this investigation, his identity is increasingly confused with that of his grandfather, so that, at the end of the novel, the central character performs the figure of his ancestor, marked by a violent behavior. Without this performance, the protagonist would not be able to execute a regulatory practice characteristic of masculinity: violence, and it is from it that the protagonist ratifies his place as a man in the family. Thus, it is clear how the conflicts that the main characters experience are very much linked to male identity issues; or rather, of certain patterns of masculinity imposed on male subjects, so that it can be said that, in these two novels, the male characters are men adrift.